Growing in the city: Urban evolutionary ecology of avian growth rates. (17th September 2020) - Corsini, Michela; Schöll, Eva Maria; Di Lecce, Irene; Chatelain, Marion; Dubiec, Anna; Szulkin, Marta
Abstract: Introduction: Rapid environmental change driven by urbanization offers a unique insight into the adaptive potential of urban‐dwelling organisms. Urban‐driven phenotypic differentiation is increasingly often demonstrated, but the impact of urbanization (here modelled as the percentage of impervious surface (ISA) around each nestbox) on offspring developmental rates and subsequent survival remains poorly understood. Furthermore, the role of selection on urban‐driven phenotypic divergence was rarely investigated to date. Methods and Results: Data on nestling development and body mass were analysed in a gradient of urbanization set in Warsaw, Poland, in two passerine species: great tits ( Parus major ) and blue tits ( Cyanistes caeruleus ). Increasing levels of impervious surface area (ISA) delayed the age of fastest growth in blue tits. Nestling body mass was also negatively affected by increasing ISA 5 and 10 days after hatching in great tits, and 10 and 15 days in blue tits, respectively. High levels of ISA also increased nestling mortality 5 and 10 days after hatching in both species. An analysis of selection differentials performed for two levels of urbanization (low and high ISA) revealed a positive association between mass at day 2 and survival at fledging. Discussion: This study confirms the considerable negative impact of imperviousness—a proxy for urbanization level—on offspring development, body mass and survival, and highlights increased selection on avian mass at hatching in a high ISA environment.